2017
DOI: 10.1038/s41598-017-15423-4
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS guided isolation of three pairs of enantiomeric alkaloids from Macleaya cordata and their enantioseparations, antiproliferative activity, apoptosis-inducing property

Abstract: (±)-Macleayins F-H (1-3), three pairs of new enantiomeric alkaloid dimers, along with four known alkaloids (4-7) as their plausible biogenetic precursors, were isolated from the aerial parts of Macleaya cordata. Compounds 1-3 were obtained under the guidance of LC-MS investigation, and their structures were elucidated by analysis of the 1D and 2D NMR spectroscopic data. The racemic mixtures were successfully separated by chiral HPLC, and the absolute configurations of enantiomers were determined by electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…Based on the previous strategy and comparison with the literature, compound 93 was identified as (±)‐bocconarborine A. Similarly, compounds 42 , 43 , 91 , 92 , 94 and 95 were identified as (±)‐macleayins A, (+)‐macleayin G, (±)‐macleayins B, chelidimerine, sanguinarine‐methylene‐chelerythrine and chelerythrine‐methylene‐chelerythrine, respectively, which are in agreement with the literature 45,46 …”
Section: Resultssupporting
confidence: 83%
“…Based on the previous strategy and comparison with the literature, compound 93 was identified as (±)‐bocconarborine A. Similarly, compounds 42 , 43 , 91 , 92 , 94 and 95 were identified as (±)‐macleayins A, (+)‐macleayin G, (±)‐macleayins B, chelidimerine, sanguinarine‐methylene‐chelerythrine and chelerythrine‐methylene‐chelerythrine, respectively, which are in agreement with the literature 45,46 …”
Section: Resultssupporting
confidence: 83%
“…A growing number of studies have shown that diets supplemented with oregano oil can promote performance and improve the antioxidant status and immunity of broilers [ 9 , 10 ]. Macleaya cordata is a perennial herb of the poppy family, widely distributed in southern China [ 11 ]. Previous studies have also shown that sanguinarine from macleaya cordata is the main bioactive substance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 C‐NMR (100 MHz, MeOH‐ d 4 ) δ C : 52.9 ( N ‐CH 3 ), 57.5 (8‐OCH 3 ), 62.8 (7‐OCH 3 ), 104.3 (‐OCH 2 O‐2,3), 105.0 (C‐4), 107.0 (C‐1), 119.4 (C‐11), 119.8 (C‐6a), 120.8 (C‐10), 121.7 (C‐4a), 127.0 (C‐10b), 127.3 (C‐9), 129.9 (C‐10a), 132.5 (C‐4b), 133.3 (C‐12), 134.2 (C‐12a), 147.4 (C‐7), 150.7 (C‐3), 150.9 (C‐2), 151.7 (C‐8), 152.0 (C‐6). Compared with the literature, 18,29 compounds 1 (C 20 H 14 NO 4 ) and 2 (C 21 H 18 NO 4 ) were identified as sanguinarine and chelerythrine, respectively.…”
Section: Resultsmentioning
confidence: 76%